Importance of setting an effective target market Netherlands Maritime Institute of Technology / Nurul Atikah Eka - Eka, Nurul Atikah (2018)
Target market is a particular group of consumers at which a product or service is aimed (Google, 2018). Target Marketing involves breaking a market into segments and then concentrating your marketing efforts on one or a few key segments consisting of the customers whose need and desires most closely match your product or service offerings. It can be the key to attracting new business, increasing your sales, and making your business a success.